Biotechnological and Biomedical Applications of Enzymes Involved in the Synthesis of Nucleosides and Nucleotides—2nd Edition - Jesús Fernández-Lucas (Biomolecules)
The study of nucleic acid derivatives and their role in cellular processes, first addressed in our previous Special Issue (https://www [...]